In-plane compressive behavior of a novel self-similar hierarchical honeycomb with design-oriented crashworthiness. (1st November 2021) - Liang, Hongyu; Wang, Qiang; Pu, Yongfeng; Zhao, Ying; Ma, Fangwu
Highlights: A novel self-similar hierarchical honeycomb is proposed by adding smaller hexagons in the center and the vertex position of the hexagonal honeycomb. The energy absorption mechanism of the proposed honeycomb is investigated by FEM, which is validated by theoretical results and experimental results. Two typical plateau stress regions are found under quasi-static compression, and the second plateau stress is over three times higher than the first one. The presented honeycomb is proved to absorb much more energy than the conventional HH and the vertex-based hierarchical structure with the same masses. Abstract: In order to enhance the energy absorption capacity of the honeycomb structure, a novel self-similar hierarchical honeycomb is proposed by adding smaller hexagons in the center and the vertex position of the hexagonal honeycomb (HH), and therefore named as center-vertex honeycomb (CVH). An analytical model is built to investigate the in-plane crushing responses of the newly proposed honeycomb, which is in good agreement with the simulation and experimental results. The in-plane quasi-static compression characteristics and energy absorption capabilities of CVH are investigated systematically by finite element method and are compared with that of HH and other hierarchical honeycombs. Two plateau stress regions in the stress–strain curves of CVH are found under the quasi-static compression, and the second plateau stress is over three times higher than the first one. In order to understand the strengthening mechanism clearly, stable unicellular deformation and global modes are revealed. Two typical plateau stress are deduced theoretically based on the collapse modes to achieve performance prediction, which are respectively decided by the hexagonal structures located on both sides and the six vertexes of the representative unit cell. The results show that CVH can absorb much more energy than HH and the vertex-based hierarchical structure with the same masses under quasi-static compression. Furthermore, a parametric study is performed to explore the influence of the impact velocity, the order number, and the wall thickness on the plateau stress, specific energy absorption, and collapse deformation modes of CVH. It can be concluded that CVH is a better choice for energy absorption. The present study provides significant suggestions and guidance for the design-oriented multi-stage energy absorbing reinforced honeycomb structure with special functions. Graphical abstract: Image, graphical abstract